Efficacy of Potassium Hydroxide (KOH) on the Treatment of Condyloma Acuminata - Linda Julianti Wijayadi; Kelvin Kelvin; Charity Harlim (Indonesian Journal of Global Health Research, 2025)
Condyloma acuminata (CA) represents one of the most prevalent sexually transmitted infections globally. Current treatment modalities focus primarily on lesion removal rather than viral eradication, with no universally accepted gold standard therapy. Potassium hydroxide (KOH) has emerged as a promising alternative treatment option. Objective to systematically review the efficacy and safety of potassium hydroxide in treating condyloma acuminata compared to other established treatments. A systematic literature review was conducted using PubMed, Google Scholar, Science Direct, Wiley Online Library, and Cochrane Library databases. Search terms included combinations of "potassium hydroxide," "KOH," "condyloma acuminata," and "genital warts." Studies published within the last decade comparing KOH with other established treatments were included. From 1195 articles screened, 5 articles were finally obtained on 2014 to 2025. Screening was performed by the authors using Mendeley Reference Manager. Five comparative studies involving 351 patients were analyzed. KOH 5% solution achieved complete response rates ranging from 65% to 88.9%, comparable to established treatments including cryotherapy (54.7-72.3%), trichloroacetic acid (78.6%), and CO₂ laser therapy (88.9%). KOH demonstrated shorter treatment duration and lower recurrence rates in several studies. The safety profile was favorable, with common adverse effects being superficial erosions (14-50%), mild burning sensation, and transient erythema. A 5% potassium hydroxide solution demonstrates comparable efficacy to established therapies, with potential advantages including a shorter treatment duration, patient self-application capability, and a favorable safety profile. KOH represents a viable treatment option for condyloma acuminata, particularly valuable in resource-limited settings.